Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 69

Answer

$\dfrac{4}{3x^{2}+8x-3}+\dfrac{2}{3x^{2}-7x+2}=\dfrac{2}{(x+3)(x-2)}$

Work Step by Step

$\dfrac{4}{3x^{2}+8x-3}+\dfrac{2}{3x^{2}-7x+2}$ Factor both denominators: $\dfrac{4}{(x+3)(3x-1)}+\dfrac{2}{(3x-1)(x-2)}=...$ Evaluate the sum: $...=\dfrac{4(x-2)+2(x+3)}{(x+3)(x-2)(3x-1)}=\dfrac{4x-8+2x+6}{(x+3)(x-2)(3x-1)}=...$ $...=\dfrac{6x-2}{(x+3)(x-2)(3x-1)}=...$ Take out common factor $2$ from the numerator and simplify: $...=\dfrac{2(3x-1)}{(x+3)(x-2)(3x-1)}=\dfrac{2}{(x+3)(x-2)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.